The Impact of Performance-Based Assessment on Academic Writing Instruction - Dewi, Anita Candra; Sheik Mohamed; Kh. Atikur Rahman; Luís Miguel Oliveira de Barros Cardoso (Inspiring: English Education Journal, 2024)
This study seeks to determine the positive impact of PBA, which synchronizes student achievement in the learning process with final grades. Performance-Based Assessment (PBA) is a pedagogical strategy used to achieve student targets in the following learning objectives, especially in Academic Writing courses that aim to make students competent novice writers. The Performance-Based Assessment teaching style allows students to write seminar-ready draft proposals at the end of the Academic Writing course. It was decided to adopt a single case study research design to get more thorough data about the respondents. This study used Performance-Based Assessment (PBA) in academic writing classes. This study shows that Performance-Based Assessment improves student learning, notably in Academic Writing, proving that PBA is a good teaching method.